Pengaruh Lingkungan Kerja dan Budaya Organisasi Terhadap Kepuasan Kerja Karyawan pada PT X - Jessica Tania Putri; Agung Wahyu Handaru; Christian Wiradendi Wolor (Teewan Journal Solutions, 2025)
The objectives of this study were: 1) To analyze and determine the effect between the work environment on employee job satisfaction at PT “X”. 2) To analyze and determine the effect between organizational culture on employee job satisfaction at PT “X”. 3) To analyze and determine the effect of work environment and organizational culture on employee job satisfaction at PT “X”. This research was conducted on 46 employees of PT “X”. The data collection technique used a survey method through distributing questionnaires and processed using SPSS (Statistical Product and Service Solutions) version 27 as software in processing and analysis. This research uses descriptive analysis. The results obtained from regression analysis show that there is a positive and significant influence between the work environment and organizational culture on employee job satisfaction. The work environment model and organizational culture simultaneously have a significant effect on job satisfaction in PT “X” employees with an Fhitung > Ftabel value of 31.845 > 3.21 and the significance value obtained is smaller than 0.05, namely 0.001 < 0.05.